4(v+1)-v=3(v+1)+3

Simple and best practice solution for 4(v+1)-v=3(v+1)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(v+1)-v=3(v+1)+3 equation:



4(v+1)-v=3(v+1)+3
We move all terms to the left:
4(v+1)-v-(3(v+1)+3)=0
We add all the numbers together, and all the variables
-1v+4(v+1)-(3(v+1)+3)=0
We multiply parentheses
-1v+4v-(3(v+1)+3)+4=0
We calculate terms in parentheses: -(3(v+1)+3), so:
3(v+1)+3
We multiply parentheses
3v+3+3
We add all the numbers together, and all the variables
3v+6
Back to the equation:
-(3v+6)
We add all the numbers together, and all the variables
3v-(3v+6)+4=0
We get rid of parentheses
3v-3v-6+4=0
We add all the numbers together, and all the variables
-2!=0
There is no solution for this equation

See similar equations:

| x+7=-3x-29 | | 6y-7/4=-3/4y-1/3 | | 4(u-1)-4=-2(-6u+7)-4u | | 3(2x-4)+12x=30 | | 2(u+1)+8=9(2u+4) | | 42=-6r-18 | | x+23=5x-1 | | 42=-6r–18 | | -2(x-4)=4x-14 | | 4x-3-5x+11=15x+16 | | y=−4 | | 4w-8=-56 | | 3(x-2)=5x=9-4(x=3) | | x*6=186 | | -4w–8=-56 | | 1/3*2x+9)=2/3x | | 4x-18=-3x-8 | | -2(x-4)=9x-14 | | -10=-4v+9v | | -4(z-6)=8 | | -4(z–6)=8 | | -4(-6x+2)-2x=4(x-3)-5 | | (3^x+1)=28 | | 9x+17=-17+9x | | 2(2x+1)=10x | | 2s+6=5 | | 13x-9=7x+15 | | s+44=-1 | | t=55-9-3 | | 2(2-6x)=-4(3x-1) | | 40=-9q+q | | 57=10p+9p |

Equations solver categories